Scientific updates on vitamin D, folic acid and magnesium deficiency in depression (Research, Society and Development, 2021)
Objective: to carry out a literature review about the influence of vitamin D, methylfolate and magnesium deficiency in the development of depression. Methodology: An integrative review was carried out, with studies published between 2016 and 2020. Initially, the guiding question was established, followed by the selection of the descriptors “Vitamin D deficiency”; “Folic acid”, “magnesium deficiency” and “depression”, according to the Health Sciences Descriptors platform. The databases for the search for publications were Scielo, Medline, Lilacs and Pubmed. Then, the exclusion and inclusion criteria for publications were defined. Results and Discussion: Thus, based on the methodological protocol employed, 24 articles were selected to compose the study. Most (n = 19, 79.17%) correspond to publications that have somehow evaluated the relationship between vitamin D and depression. Four (16.66%) studies correspond to the ratio of folic acid, and one (4.17%) to the role of magnesium in depressive disorders. Many authors have observed that vitamin D deficiency is associated with the presence of depressive symptoms. However, there was a scarcity of scientific studies aimed at assessing the influence of folic acid and magnesium deficiency on the development of depression. Conclusion: it was found that most studies focus on the association between the absence of vitamin D and depression, showing that many researchers see this micronutrient as an element involved in such a disorder. However, it is emphasized the need for further investigations that aim to collaborate with the understanding of the role of folate and magnesium in mood changes.